A Meta-Study of the Evolutionary Transformative Academic Landscape by Artificial Intelligence and Machine Learning - Lainjo, Bongs; Tmouche, Hanan (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
This article titled “The Evolutionary Transformative Academic Landscape by Artificial Intelligence and Machine Learning (Meta-Study)